Age-related changes in the response of intestinal cells to 1α,25(OH)2-vitamin D3 - González Pardo, María Verónica (2013)
The hormonally active form of vitamin D3, 1α,25(OH)2-vitamin D3, acts in intestine, its major target tissue, where its actions are of regulatory and developmental importance: regulation of intracellular calcium through modulation of second messengers and activation of mitogenic cascades leading to cell proliferation. Several causes have been postulated to modify the hormone response in intestinal cells with ageing, among them, alterations of vitamin D receptor (VDR) levels and binding sites, reduced expression of G-proteins and hormone signal transduction changes. The current review summarizes the actual knowledge regarding the molecular and biochemical basis of age-impaired 1α,25(OH)2-vitamin D3 receptor-mediated signaling in intestinal cells. A fundamental understanding why the hormone functions are impaired with age will enhance our knowledge of its importance in intestinal cell physiology.